A novel approach for modeling retained austenite transformations during rolling contact fatigue. Issue 4 (4th October 2017) - Morris, D.; Sadeghi, F.; Chen, Y.‐C.; Wang, C.; Wang, B.
Abstract: Retained austenite (RA) transformation in martensitic steels subjected to rolling contact fatigue (RCF) is a well‐established phenomenon. In this investigation, a novel approach is developed to predict martensitic transformations of RA in steels subjected to RCF. In order to achieve the objectives, a 2‐dimensional finite element model was developed to determine subsurface stresses due to rolling contact. These stresses are utilized within a continuum damage mechanics framework to determine RA transformations as a function of depth and cycles. Phase transformations were determined by comparing the required thermodynamic driving force for transformations to the energy dissipation of the microstructure. The results obtained from the combined FEA and continuum damage mechanics model were corroborated to the experimental results for RA decomposition as a function of depth and cycle for SAE 52100 steel. The results obtained are in good agreement with observed RA decomposition and DER formation as compared with the experimental results.